The Influence of Professional Ethics and Emotional Intelligence Implementation on Auditor Performance - Mahmud Mahmud; Budi Eko Soetjipto; Cipto Wardoyo (Journal of Social Science, 2022)
is study aims to determine the effect of professional ethics and emotional intelligence on the performance of auditors at the District Inspectorate Office Dompu.The method used in this study is a quantitative method with a descriptive and associative approach using primary data. Statistical analysis used in this research is validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis, hypothesis testing using t-test and f test and coefficient of determination analysis with the help of the SPSS program. The study results reveal: 1) professional ethics and emotional intelligence have a simultaneous effect on auditor performance. The Fable value of 3.24 is more minor than the Fount of 39.810, with a significant value less than 0.05, which is 0.000. 2) professional ethics and emotional intelligence significantly affect auditor performance with the result that the t value on professional ethics is 3.513, which means that the t count is more significant than the t table of 1.68595 and has a significant level of 0.05. This shows that the professional ethics variable positively affects auditor performance. The t value of emotional intelligence is 4.285, with a significance value of 0.032. In other words, the emotional intelligence variable positively affects auditor performance. So that future researchers can add or respond to other variables besides professional ethics and emotional intelligence on auditor performance to realize even better research.